Simulating an ageing population a microsimulation approach applied to Sweden - Klevmarken, Anders, 1941-; Lindgren, Björn, 1942- (Emerald, 2008)
The book series Contributions to Economic Analysis was established under the editorship of Jan Tinbergen in 1952. Its purpose ever since has been to stimulate the international exchange of scientific information and to reinforce international cooperation by publishing original research in applied economics. The editors and authors of the series represent a broad range of geographic and subject matter interests in economics, and the series includes books from all areas of macroeconomics and microeconomics. These books have in common a quantitative approach to economic problems of practical importance.
Includes index.
Keywords: Older people -- Sweden.; elektronické knihy; electronic books